The Potential Of Purple Leaves Ethanol Extract (Graptophyllum pictum L.) Against The Growth Of Staphylococcus aureus and Candida albicans - Noor Hujjatusnaini; Yunia Dwi Friska; Ayatus saadah; Astuti Muh. Amin (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
The Potential of Purple Leaves Ethanol Extract (Graptophyllum pictum L.) against Staphylococcus aureus and Candida albicans. This study is an experimental study with a comparative approach, aimed at analyzing the potential of purple leaves (Graptophyllum pictum L.) by using in vitro method against Staphylococcus aureus and Candida albicans. The clear zone was formed between the outer sides of the paper disc containing the ethanolic extract of the purple leaves (Graptophyllum pictum L.) and the S. column. gold and C. albicans colonies are growth indicators. The growth of S. aureus and C. albicans were measured at incubation time 24, 48, and 72 hours, which were then analyzed by analysis with Anava's one-way statistical test and continued with Duncan's 1%. The research found that the purple leaves ethanol extract (Graptophyllum pictum L.) has the growth inhibition of Staphylococcus aureus and Candida albicans, which is indicated by the comparison results of the optimal concentrations of S. aureus and C. albicans, were 50% and 90%, so that the purple leaf ethanol extract could recommended as an antibacterial.